Point Free problems in Haskell - haskell

I am trying to convert the following Haskell code to point free style, to no avail.
bar f g xs = filter f (map g xs )
I'm new to Haskell and any help would be great.

Converting to pointfree style can be done entirely mechanically, though it's hard without being comfortable with the fundamentals of Haskell syntax like left-associative function application and x + y being the same as (+) x y. I will assume you are comfortable with Haskell syntax; if not, I suggest going through the first few chapters of LYAH first.
You need the following combinators, which are in the standard library. I have also given their standard names from combinator calculus.
id :: a -> a -- I
const :: a -> b -> a -- K
(.) :: (b -> c) -> (a -> b) -> (a -> c) -- B
flip :: (a -> b -> c) -> (b -> a -> c) -- C
(<*>) :: (a -> b -> c) -> (a -> b) -> (a -> c) -- S
Work with one parameter at a time. Move parameters on the left to lambdas on the right, e.g.
f x y = Z
becomes
f = \x -> \y -> Z
I like to do this one argument at a time rather than all at once, it just looks cleaner.
Then eliminate the lambda you just created according to the following rules. I will use lowercase letters for literal variables, uppercase letters to denote more complex expressions.
If you have \x -> x, replace with id
If you have \x -> A, where A is any expression in which x does not occur, replace with const A
If you have \x -> A x, where x does not occur in A, replace with A. This is known as "eta contraction".
If you have \x -> A B, then
If x occurs in both A and B, replace with (\x -> A) <*> (\x -> B).
If x occurs in just A, replace with flip (\x -> A) B
If x occurs in just B, replace with A . (\x -> B),
If x does not occur in either A or B, well, there's another rule we should have used already.
And then work inward, eliminating the lambdas that you created. Lets work with this example:
f x y z = foo z (bar x y)
-- Move parameter to lambda:
f x y = \z -> foo z (bar x y)
-- Remember that application is left-associative, so this is the same as
f x y = \z -> (foo z) (bar x y)
-- z appears on the left and not on the right, use flip
f x y = flip (\z -> foo z) (bar x y)
-- Use rule (3)
f x y = flip foo (bar x y)
-- Next parameter
f x = \y -> flip foo (bar x y)
-- Application is left-associative
f x = \y -> (flip foo) (bar x y)
-- y occurs on the right but not the left, use (.)
f x = flip foo . (\y -> bar x y)
-- Use rule 3
f x = flip foo . bar x
-- Next parameter
f = \x -> flip foo . bar x
-- We need to rewrite this operator into normal application style
f = \x -> (.) (flip foo) (bar x)
-- Application is left-associative
f = \x -> ((.) (flip foo)) (bar x)
-- x appears on the right but not the left, use (.)
f = ((.) (flip foo)) . (\x -> bar x)
-- use rule (3)
f = ((.) (flip foo)) . bar
-- Redundant parentheses
f = (.) (flip foo) . bar
There you go, now try it on yours! There is not really any cleverness involved in deciding which rule to use: use any rule that applies and you will make progress.

Both of the existing answers don't really answer your specific question in a way that's elucidating: one is "here are the rules, work it out for yourself" and the other is "here is the answer, no information about how the rules generate it."
The first three steps are really easy and consist in removing a common x from something of the form h x = f (g x) by writing h = f . g. Essentially it's saying "if you can write the thing in the form a $ b $ c $ ... $ y $ z and you want to remove the z, change all the dollars to dots, a . b . c . ... . y:
bar f g xs = filter f (map g xs)
= filter f $ (map g xs)
= filter f $ map g $ xs -- because a $ b $ c == a $ (b $ c).
bar f g = filter f . map g
= (filter f .) (map g)
= (filter f .) $ map $ g
bar f = (filter f .) . map
So this last f is the only tricky part, and it's tricky because the f is not at the "end" of the expression. But looking at it, we see that this is a function section (. map) applied to the rest of the expression:
bar f = (.) (filter f) . map
bar f = (. map) $ (.) $ filter $ f
bar = (. map) . (.) . filter
and that's how you reduce an expression when you don't have complicated things like f x x and the like appearing in it. In general there is a function flip f x y = f y x which "flips arguments"; you can always use that to move the f to the other side. Here we have flip (.) map . (.) . filter if you include the explicit flip call.

I asked lambdabot, a robot who hangs out on various Haskell IRC channels, to automatically work out the point-free equivalent. The command is #pl (pointless).
10:41 <frase> #pl bar f g xs = filter f (map g xs )
10:41 <lambdabot> bar = (. map) . (.) . filter
The point free version of bar is:
bar = (. map) . (.) . filter
This is arguably less comprehensible than the original (non-point-free) code. Use your good judgement when deciding whether to use point-free style on a case-by-case basis.
Finally, if you don't care for IRC there are web-based point-free
converters such as pointfree.io, the pointfree command line program, and other tools.

Related

Haskell dot operator with sort and (++) [duplicate]

This question already has answers here:
Haskell function composition operator of type (c→d) → (a→b→c) → (a→b→d)
(6 answers)
Closed last year.
I am learning haskell at the moment and trying to figure out all the rules of prefix, infix, precedence, etc.
While trying to implement a function which appends two lists and sorts them I started with:
appendAndSort :: [a] -> [a] -> [a]
appendAndSort = sort . (++)
which does no compile.
Following:
appendAndSort :: Ord a => [a] -> [a] -> [a]
appendAndSort = (sort .) . (++)
on the other hand does work.
Why do I have to add a second dot at sort and parentheses around it?
Let's start with a version that uses explicit parameters.
appendAndSort x y = sort (x ++ y)
Writing ++ as a prefix function rather than an operator yields
appendAndSort x y = sort ((++) x y)
Knowing that (f . g) x == f (g x), we can identify f == sort and g == (++) x to get
appendAndSort x y = (sort . (++) x) y
which lets us drop y as an explicit parameter via eta conversion:
appendAndSort x = sort . (++) x
The next step is to repeat the process above, this time with (.) as the top most operator to write as a prefix function,
appendAndSort x = (.) sort ((++) x)
then apply the definition of . again with f == (.) sort and g == (++):
appendAndSort x = (((.) sort) . (++)) x
and eliminate x via eta conversion
appendAndSort = ((.) sort) . (++)
The last step is to write (.) sort as an operator section, and we're done with our derivation.
appendAndSort = (sort .) . (++)
The expression (f . g) x means f (g x).
Coherently, (f . g) x y means f (g x) y.
Note how y is passed as a second parameter to f, not to g. The result is not f (g x y).
In your case, (sort . (++)) x y would mean sort ((++) x) y, which would call sort with first argument (++) x (the function which prepends the list x to its list argument), and with second argument y. Alas, this is ill-typed since sort only takes one argument.
Consequently, this is also invalid
appendAndSort x y = (sort . (++)) x y
hence so is this
appendAndSort = sort . (++)
By contrast, ((f .) . g) x y does work as expected. Let's compute:
((f .) . g) x y
= -- same reasoning as above, y is passed to (f.), not g
(f .) (g x) y
= -- application associates on the left
((f .) (g x)) y
= -- definition of `(f.)`
(f . (g x)) y
= -- definition of .
f ((g x) y)
= -- application associates on the left
f (g x y)
So this really makes y to be passed to g (and not f).
In my opinion the "idiom" (f .) . g isn't worth using. The pointful \x y -> f (g x y) is much simpler to read, and not terribly longer.
If you really want, you can define a custom composition operator to handle the two-argument case.
(.:) f g = \x y -> f (g x y)
Then, you can write
appendAndSort = sort .: (++)

Notational confusion in a basic type declaration exercise

I'm going through the new book Haskell Programming from First Principles. It seems decent, but I feel that there are some confusing holes in the explanations. I apologize if I'm missing something basic.
The last problem in chapter 5 is to fill in the ??? below so that things make sense:
munge :: (x -> y) -> (y -> (w, z)) -> x -> w
munge = ???
The solution which was explained to me (after much head-scratching) goes:
g :: y -> (w, z)
g = undefined
f :: x -> y
f = undefined
munge :: (x -> y) -> (y -> (w, z)) -> x -> w
munge g f v = fst (g (f v))
I'm getting hung up on this example in two ways.
First, it seems like the munge function ought to take a function as input which takes x -> y. But the way munge is defined, it seems like we supply an additional argument v to the function f first. But if f :: x -> y, then won't the expression f v be of type just y instead of x -> y?
Second, I'm struggling to understand why the x appears in the second-to-last position in the type declaration. At that point I feel like the logical next piece after the (y -> (w,x)) step should just be w, since at that stage the function g is being applied to fst and w ought to be the type of what fst returns. I can feel that I'm close, but can't quite close the gap.
Clearly I'm not understanding the notation correctly. Can anyone set me straight?
EDIT: Ok, here is a clarifying question to the second part. Is it possible to revise the munge function so that it has the following type (i.e. original type with second-to-last x application omitted)? If so what would it look like?
munge :: (x -> y) -> (y -> (w, z)) -> w
The answer is incorrect and ill-typed. f and g should be swapped:
munge :: (x -> y) -> (y -> (w, z)) -> x -> w
munge g f v = fst (f (g v))
I'm not sure if that clears up your confusion.
EDIT In case it's interesting, here are more equivalent ways of writing this function and its type:
-- notice parens in type signature; `->` associates right
munge :: (x -> y) -> ((y -> (w, z)) -> (x -> w))
munge g f v = -- omitted
-- type signature omitted
munge boop _plort zOWY = fst (_plort (boop zOWY))
munge g f = fst . f . g
munge g = \f v -> fst . f . g $ v
-- don't do this please
munge = ((fst .) .) . (.)
EDIT2 It might be helpful to play around with this in GHCi, asking the inferred type of different expressions:
Prelude> let munge g f v = fst (f (g v))
Prelude> :t munge
munge :: (t1 -> t) -> (t -> (a, b)) -> t1 -> a
Prelude> :t munge head
munge head :: (t -> (a, b)) -> [t] -> a
Prelude> :t munge head (\x-> (x, not x))
munge head (\x-> (x, not x)) :: [Bool] -> Bool
Prelude> :t munge ((+1) . fst . snd . head)
munge ((+1) . fst . snd . head)
:: Num t => (t -> (a, b)) -> [(a1, (t, b1))] -> a
The solution, confusingly, is using the same variables f and g for two different things: as global names for two functions, and as parameter names in defining munge. Making a change of variable should make it clearer:
g :: y -> (w, z)
g = undefined
f :: x -> y
f = undefined
munge :: (x -> y) -> (y -> (w, z)) -> x -> w
munge f1 f2 v = fst (f2 (f1 v)) -- fst . f2 . f1 $ v
Then you would call munge on f and g will thing like
munge f g someArgumentForF
Inside munge, f (called f1) is first applied to someArgumentForF (called v) to get a value that can be passed to g (called f2). This produces a tuple, and applying fst to the tuple returns the value of type w needed as the final result.

Haskell - How to write (.) f f = (\x -> f (f x))

I need to write on a module to be run on GHCi, with a function composition to the same function. This (The classic fog(x) = f(g(x))) runs:
(.) f g = (\x -> f (g x)).
The problem appears when I try to write it like this
(.) f f = (\x -> f (f x)). (fof(x) = f(f(x)))
GHCi says:
"Conflicting definitions for `f'
Bound at: Lab1.hs:27:9
Lab1.hs:27:12"
Line 27:9 appear on the first time f and line 27:12 appear f again.
Why doesn't Haskell understand (.) f f = (\x -> f (f x))?
In Haskell, arguments to a function must have unique names. Using the same name for another argument is not allowed. This is because
foo x y = ... === foo = (\x-> (\y-> ...))
and if y where replaced with x, the second x would just shadow the first inside the ... body: there would be no way to reference the first x from there.
You can just define twice f x = f (f x):
Prelude> :t twice
twice :: (t -> t) -> t -> t
Prelude> twice (+1) 4
6
Alternatively, f (f x) = (.) f f x = join (.) f x:
Prelude Control.Monad> :t join (.)
join (.) :: (b -> b) -> b -> b
join is defined in Control.Monad. For functions, it holds that join g x = g x x. It is also known as W combinator.
E.g. print $ join (.) (+1) 4 prints 6.
As the error message says, you have conflicting definitions for f in the definition (.) f f = (\x -> f (f x)). You are binding the name f to both the first and second arguments to (.), so ghci doesn't know which argument to use when evaluating the expression f x.
There is nothing wrong with defining (.) using the pattern (.) f g, and then calling it with two arguments that happen to be the same.

Haskell - How to write twice function using (.) f g - function composition

Here is the problem, i need to write the well known twice function
(twice= \x-> \x-> x)
but this time using (.) composition function like (.) f g.
I don't know how to solve it, cause I thought at the beginning to do like:
(.) f g = (\x -> f (g x))
with (g = f) so it would be like this
(.) f f = (\x -> f (f x))
but I have a
"Conflicting definitions for `f'"
running on GHCI
So, any suggestions ?
I don't know how you got anything other than a parse input from this:
(.) f f = (\x -> f (f x))
but the definition you gave: twice = \x -> \x -> x has nothing to do with using something "twice" - indeed if you plug in some values:
twice a b
= (\x -> \x -> x) a b
= (\x -> (\x -> x)) a b -- (rename the inner x)
= (\x -> (\y -> y)) a b
= ((\x -> (\y -> y)) a) b
= (\y -> y) b
= b
and indeed GHCi will tell you the same:
> let twice = \x -> \x -> x
> :t twice
twice :: t -> t1 -> t1
> twice "a" "b"
"b"
Now I guess you want something like this:
let twice f x = f (f x)
for example:
> let twice f x = f (f x)
> twice (+1) 5
7
as you can see twice (+1) adds 2 (or twice one).
Now how can you do this using (.)? - Well your intuition was wright:
> let twice f = f . f
> twice (+1) 5
7
concerning a module
As you asked for a module - this compiles (and loads into GHCi) fine on my system(s):
module Twice where
twice :: (a->a) -> a -> a
twice f = f . f
remark:
this only works if you include (.) from the prelude (or GHC.Base) - I suspect that you got some kind of excercise that hid the prelude - in this case you have to define (.) for yourself first (most likely another excercise)
if you need to implement it yourself:
(.) :: (b -> c) -> (a -> b) -> a -> c
(.) g f x = g (f x)

What is a general scheme for writing a function in pointfree style?

I am working through the 20 Intermediate Haskell Exercises at the moment, which is quite a fun exercise. It involves implementing various instances of the typeclasses Functor and Monad (and functions that takes Functors and Monads as arguments) but with cute names like Furry and Misty to disguise what we're doing (makes for some interesting code).
I've been trying to do some of this in a point-free style, and I wondered if there's a general scheme for turning a point-ful (?) definition into a point-free definition. For example, here is the typeclass for Misty:
class Misty m where
unicorn :: a -> m a
banana :: (a -> m b) -> m a -> m b
(the functions unicorn and banana are return and >>=, in case it's not obvious) and here's my implementation of apple (equivalent to flip ap):
apple :: (Misty m) => m a -> m (a -> b) -> m b
apple x f = banana (\g -> banana (unicorn . g) x) f
Later parts of the exercises have you implement versions of liftM, liftM2 etc. Here are my solutions:
appleTurnover :: (Misty m) => m (a -> b) -> m a -> m b
appleTurnover = flip apple
banana1 :: (Misty m) => (a -> b) -> m a -> m b
banana1 = appleTurnover . unicorn
banana2 :: (Misty m) => (a -> b -> c) -> m a -> m b -> m c
banana2 f = appleTurnover . banana1 f
banana3 :: (Misty m) => (a -> b -> c -> d) -> m a -> m b -> m c -> m d
banana3 f x = appleTurnover . banana2 f x
banana4 :: (Misty m) => (a -> b -> c -> d -> e) -> m a -> m b -> m c -> m d -> m e
banana4 f x y = appleTurnover . banana3 f x y
Now, banana1 (equivalent to liftM or fmap) I was able to implement in pointfree style, by a suitable definition of appleTurnover. But with the other three functions I've had to use parameters.
My question is: is there a recipe for turning definitions like these into point-free definitions?
As demonstrated by the pointfree utility, it's possible to do any such conversion automatically. However, the result is more often obfuscated than improved. If one's goal is to enhance legibility rather than destroy it, then the first goal should be to identify why an expression has a particular structure, find a suitable abstraction, and build things up that way.
The simplest structure is simply chaining things together in a linear pipeline, which is plain function composition. This gets us pretty far just on its own, but as you noticed it doesn't handle everything.
One generalization is to functions with additional arguments, which can be built up incrementally. Here's one example: Define onResult = (. (.)). Now, applying onResult n times to an initial value of id gives you function composition with the result of an n-ary function. So we can define comp2 = onResult (.), and then write comp2 not (&&) to define a NAND operation.
Another generalization--which encompasses the above, really--is to define operators that apply a function to a component of a larger value. An example here would be first and second in Control.Arrow, which work on 2-tuples. Conal Elliott's Semantic Editor Combinators are based on this approach.
A slightly different case is when you have a multi-argument function on some type b, and a function a -> b, and need to combine them into a multi-argument function using a. For the common case of 2-ary functions, the module Data.Function provides the on combinator, which you can use to write expressions like compare `on` fst to compare 2-tuples on their first elements.
It's a trickier issue when a single argument is used more than once, but there are meaningful recurring patterns here that can also be extracted. A common case here is applying multiple functions to a single argument, then collecting the results with another function. This happens to correspond to the Applicative instance for functions, which lets us write expressions like (&&) <$> (> 3) <*> (< 9) to check if a number falls in a given range.
The important thing, if you want to use any of this in actual code, is to think about what the expression means and how that's reflected in the structure. If you do that, and then refactor it into pointfree style using meaningful combinators, you'll often make the intent of the code clearer than it would otherwise be, unlike the typical output of pointfree.
Yes! One of the tricks is to write your dots in prefix notation rather than infix. Then you should be able to find new things that look like function composition. Here's an example:
banana2 f = appleTurnover . banana1 f
= (.) appleTurnover (banana1 f)
= ((.) appleTurnOver) . banana1 $ f
banana2 = (appleTurnover .) . banana1
The source code for the pointfree utility contains more, but this one handles a lot of cases.
banana4 f x y = appleTurnover . banana3 f x y
= (.) appleTurnover ((banana3 f x) y)
= ((.) appleTurnover) . (banana3 f x) $ y
banana4 f x = ((.) appleTurnover) . (banana3 f x)
= (.) ((.) appleTurnover) (banana3 f x)
= ((.) ((.) appleTurnover)) ((banana3 f) x)
= ((.) ((.) appleTurnover)) . (banana3 f) $ x
banana4 f = ((.) ((.) appleTurnover)) . (banana3 f)
= (.) ((.) ((.) appleTurnover)) (banana3 f)
= ((.) ((.) ((.) appleTurnover))) (banana3 f)
= ((.) ((.) ((.) appleTurnover))) . banana3 $ f
banana4 = ((.) ((.) ((.) appleTurnover))) . banana3
= (((appleTurnover .) .) .) . banana3
I use the following term rewrite system:
\x -> f x ------> f
f y x ----------> flip f x y
\x -> f (g x) --> f . g
It is incomplete (read why in books about combinatory logic), but it's enough:
Here is banana2:
banana2 f = appleTurnover . banana1 f
Rewrite as a lambda:
banana2 = \f -> appleTurnover . banana1 f
Write (.) in prefix style:
banana2 = \f -> (.) appleTurnover (banana1 f)
Note that
banana2 = \f -> ((.) appleTurnover) (banana1 f)
So rule 3 can be applied. f is (.) appleTurnover and g is banana:
banana2 = ((.) appleTurnover) . banana1
There is a pointfree package which takes a Haskell function definition and attempts to re-write it in a pointfree style. I'd suggest experimenting with it to get new ideas. See this page for more details; the package is available here.
Since pointfree style is combinators style, just apply known combinators definitions, reading them backwards to make the substitution:
B f g x = f (g x) -- (.) , <$> for ((->) a)
C f x y = f y x -- flip
K x y = x -- const
I x = x -- id
S f g x = f x (g x) -- <*> , ap for ((->) a)
W f x = f x x -- join
(f >>= g) x = g (f x) x
(f =<< g) x = f (g x) x
At times liftMx, liftAx, sequence, sequenceA can simplify things. I'd also consider foldr, unfoldr, iterate, until etc. as basic combinators.
Often, using operator sections helps too:
op a b = (a `op` b) = (`op` b) a = (a `op`) b
Some patterns can become familiar and so, used directly:
((f .) . g) x y = f (g x y)
((. f) . g) x y = g x (f y)
(((f .) .) . g) x y z = (f .) (g x y) z = f (g x y z)
(((. f) .) . g) x y z = (. f) (g x y) z = g x y (f z)
etc.

Resources